Code-Switching as Cultural Expression among Indonesian Social Media Users through Social Media Data - Ramadhan, Muhammad Iqbal; Fernanda, Muhammad Sandy; Swasono, Endratno Pilih (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
In Indonesia, code-switching is commonly used, especially in a phenomenon known as Jaksel language, a mix of Indonesian and English that people use in everyday communication. Most studies on code switching have looked at how it works and why people do it. Not many have thought about how it helps people show their culture. This study wants to see how people in Indonesia who use social media use code switching to show who they are and what they believe in when they are online. Data were collected from posts on Instagram and TikTok to analyze how they use language and what that says about what they think and where they fit in. What we found out is that code switching is not only a way to communicate, but it is also a way for people to express their feelings, show who they are, and fit in with what is cool online. When people use English, it can sound calmer and not as emotional, whereas when they use Indonesian, it keeps them connected to their culture. This study shows that the Jaksel language is a way that young people in Indonesia express themselves and their culture, and it is shaped by the world getting smaller and social media. So this study helps us better understand code-switching, especially how young people use it to express who they are and how they communicate online. The Jaksel language is a part of this, and code switching is a key aspect of the Jaksel language.